Polemik Faktualitas Kisah Al-Quran - Muhammad Amin (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2022)
This article is aimed to study the discussionsbetween the quranic scholars, especially on the polemic of the factuality of the story of the Koran. This polemic comes as a result of the use of the literary method in the study of the story of the Koran, especially after Muhammad Ahmad Khalafullah releases his study under title al-Fann al-Qaṣaṣi fi al-Qurani al-Karīm. The Author uses the dialectical method by describing imaginary discussions among the quranic scholars in two case examples, namely the story of Ukhti Harun and Haman. The results of the author's study show that the reviewers of the story of the Koran are divided into two parts, namely believing in the factuality and historicity of the story of the Koran while others reject the factuality and historicity of the story of the Koran and only acknowledge the moral value in the story.